ANALISIS HUBUNGAN KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ADAM JAYA - Dasaad Dasaad (Jurnal Ilmiah Ekonomi Bisnis, 2015)
The performance of employee at PT Adam Jaya is considered has not been optimal. It needs an improvement through chronically resource development which is, in this case, the employee. The development includes not only technical aspects but also psychological aspects such as leadership and job satisfaction development. Leadership and job satisfaction are interrelated and important in determining the performance of an employee. High leadership will encourage the employee to work in discipline that will lead him/her to the job satisfaction. The purpose of the study is to observe the relation of leadership and the performance of employee, as well as, to observe the relation of job satisfaction and the performance of employee. The study uses questionaire, and interview and discussion. The number of respondent in this study is 60 people by proportional stratified random sampling technique. The data validity and reliability test is done with the result that each questions is valid and reliable. From the analysis statistic result, it obtains that the coefficient result between leadership and performance of employee is amounted to -0,215, while job satisfaction variable and performance of employee has corelation coefficient value as 0,173 which means that there is no corelation of the two free variables.  Keywords: leadership, job satisfation, performance of employee